Mould pressing crucible as well as preparation method and application thereof
By using expanded graphite, graphene and carbon fiber molding processes, a dense network structure is formed, which solves the problems of complex and high cost of crucible preparation process in the prior art, and improves crucible performance and production efficiency.
Patent Information
- Application Number
- CN202510175021.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-18
- Publication Date
- 2025-05-09
AI Technical Summary
In the prior art, the preparation of crucibles using chemical vapor deposition method has problems such as many process parameters, long process time, high damage rate, high energy consumption and high overall cost, and the performance of the prepared crucibles is not strengthened enough.
Expanded graphite, graphene and carbon fiber are used as raw materials to make a crucible by molding. Graphene and carbon fiber are interspersed into the pore structure of the expanded graphite during the molding process to form a dense network structure to improve the bonding interface of the material.
The crucible has been reduced in thickness, material savings, overall cost reduction, and the preparation process time is shortened and the energy consumption is low. The crucible performance reaches the index of compressive strength of 102-130MPa and flexural strength of 60-85MPa.
Smart Images

Figure CN119954523A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of crucible manufacturing, and in particular to a molded crucible and a preparation method and application thereof. Background Art
[0002] The external crucibles of existing heat fields are mostly made of carbon fiber preforms, which are formed into final products through chemical vapor deposition. The carbon-carbon crucible is thick (about 25mm) and uses a lot of materials. In terms of process, it is necessary to first use carbon fiber filaments to weave the preform, and then deposit and densify it in a high-temperature environment for a long time.
[0003] For example, CN112028657A discloses a method for preparing a carbon / carbon composite material crucible, which includes the following steps: alternately stacking multiple layers of carbon fiber plain cloth and carbon fiber mesh in sequence and compounding them by needle punching to obtain a preform; using natural gas as raw material and hydrogen or inert gas as carrier gas to perform chemical vapor deposition on the preform; subjecting the preform after chemical vapor deposition to high temperature treatment, and then mechanically processing it to the size of a crucible to obtain a prefabricated crucible; and subjecting the prefabricated crucible to chemical vapor deposition again to obtain a crucible. This technical solution requires two chemical vapor depositions, and after the first chemical vapor deposition, it is necessary to be treated in a high temperature environment of 1800℃-2400℃ before the second vapor deposition can be performed to obtain a crucible. The process parameters for the preform needle weaving and vapor deposition are many, the process time is long, the damage rate is relatively high, the energy consumption is high, and the overall cost is very high.
[0004] CN117088703A discloses a composite crucible and its preparation method and application, including the following steps: subjecting a carbon fiber preform to a first heat treatment, chemical vapor deposition and a second heat treatment in sequence to obtain a crucible blank; impregnating the crucible blank into a resin solution, and sequentially performing solidification, cracking carbonization and a third heat treatment to obtain a carbon / carbon crucible matrix; placing the carbon / carbon crucible matrix in a silicon nitride impregnation solution, and sequentially performing a PIP impregnation treatment and a fourth heat treatment to obtain a silicon carbon nitrogen crucible matrix; and subjecting the silicon carbon nitrogen crucible matrix to a silicon plating treatment to obtain the composite crucible. Similarly, the three heat treatment temperatures of this technical solution are 1800-2300°C, the chemical vapor deposition temperature is 1000-1200°C, and the deposition time is 100-300h. There are also problems such as long preparation time, high damage rate, high energy consumption, and very high overall cost.
[0005] CN101657570A discloses an expanded graphite film with improved tensile strength. In addition, a method for protecting a carbon crucible and a single product drawing device are provided. In the method for protecting a carbon crucible, the expanded graphite film with improved tensile strength is used as a middle pad of the carbon crucible, thereby significantly reducing the operation time, and can cover the inner surface of the crucible without gaps without damaging the film, and is suitable for large-scale crucibles. The expanded graphite film is characterized in that a reinforcing material composed of carbon fibers is formed in a stacked state on at least one side of a substrate composed of an expanded graphite material. The method for protecting a carbon crucible is characterized in that the expanded graphite film is sandwiched between a quartz crucible and a carbon crucible on which the quartz crucible is placed and used as a middle pad covering the inner surface of the carbon crucible. Although this technical solution no longer uses the chemical vapor deposition method to prepare the crucible, and uses expanded graphite as the middle pad of the crucible, carbon fiber is still woven in the process of preparing the expanded graphite film, and the expanded graphite film is specified as the middle pad. The operation technology is difficult, and the tensile strength of the final product is only 10-15MPa, which cannot meet the current strength requirements for crucibles.
[0006] At the same time, in the production process of negative electrode materials, the crucible in the prior art is mainly used for high-temperature processing, such as sintering and drying. Therefore, the crucible needs to withstand high temperature and high pressure to enable the negative electrode material to complete the combustion process at high temperature and form the required structure and performance. However, the crucible prepared by chemical vapor deposition in the prior art is prone to uneven heating in the local area during use, thereby affecting its service life and the processing effect of the negative electrode material.
[0007] Based on the above-mentioned prior art, the prior art uses chemical vapor deposition to prepare crucible carbon material composite crucibles, which have many process parameter requirements, long process time, relatively high damage rate, high energy consumption, high overall cost, and the crucibles prepared without using chemical vapor deposition cannot meet the relevant performance requirements, etc., which need to be solved urgently. Summary of the invention
[0008] In order to solve the above technical problems, the present invention provides a molded crucible, which is made of expanded graphite, graphene and carbon fiber as raw materials through molding, and the graphene and / or the carbon fiber are inserted into the pore structure of the expanded graphite during the molding process to obtain the molded crucible; The thickness of the crucible is 4-6 mm, the ash content is 154-205 ppm, the compressive strength is 102-130 MPa, the flexural strength is 60-85 MPa, the elastic modulus is 15-17 MPa, and the expansion coefficient is (3-4)×10 -6 / ℃, bulk density is 1.6-1.7g / cm 3 .
[0009] Further, the thickness is tested by a thickness gauge; The ash content is tested by glow discharge mass spectrometry (GDMS); The compressive strength, flexural strength and elastic modulus are tested by a universal testing machine; The expansion coefficient is tested by a thermal expansion coefficient tester; The bulk density is the ratio of the total mass to the total volume of the molded crucible.
[0010] Furthermore, the mass ratio of the expanded graphite, graphene and carbon fiber is (50-80): (10-20): (10-30).
[0011] Furthermore, the expanded graphite has a non-dense pore structure.
[0012] Furthermore, the size of the expanded graphite is 5-10 μm.
[0013] Furthermore, the expansion rate of the expanded graphite is 100-120 times.
[0014] Furthermore, the purity of the expanded graphite is ≥99.9%.
[0015] Furthermore, the number of layers of the graphene is 1-5.
[0016] Furthermore, the size of the graphene is 10-20 μm.
[0017] Furthermore, the oxygen content of the graphene is 15-20wt%.
[0018] Further, the graphene Raman test I D / I G =0.8-1.
[0019] Furthermore, the graphene has a crystallinity of 65-75%.
[0020] Furthermore, the carbon fiber is one or more of chopped carbon fiber and carbon fiber powder.
[0021] Furthermore, when the carbon fiber is chopped carbon fiber, the mass ratio of the expanded graphite, graphene and carbon fiber is (50-80): (10-20): (10-20).
[0022] Furthermore, when the carbon fiber is carbon fiber powder, the mass ratio of the expanded graphite, graphene, and carbon fiber is (50-80): (10-20): (20-30).
[0023] Furthermore, the chopped carbon fibers have a diameter of 5-15 μm and a length of 1-2 mm.
[0024] Furthermore, the carbon fiber powder has a diameter of 5-15 μm and a length of 20-200 μm.
[0025] Furthermore, when the carbon fiber includes chopped carbon fiber and carbon fiber powder, the mass ratio of the chopped carbon fiber to the carbon fiber powder is 1:2.
[0026] Furthermore, the carbon fiber is prepared using waste carbon-carbon composite materials and products recycled in the photovoltaic thermal field industry, and the carbon fiber contains 10-20wt% of silicon and / or silicon carbide.
[0027] The present invention provides a method for preparing a molded crucible, comprising the following steps: Step 1, adding expanded graphite, graphene, and carbon fiber into a mixer in the order of adding them, stirring them, and obtaining a mixture; Step 2, isostatically pressing the mixed material to obtain a crucible preform; Step 3: sintering the crucible preform to obtain the molded crucible.
[0028] Furthermore, in step 1, the stirring speed is 300-1000 r / min and the time is 2-5 h.
[0029] Furthermore, the stirring speed in step 1 is preferably 300-500 r / min.
[0030] Furthermore, the equipment used for stirring in step 1 is a powder mixer.
[0031] Furthermore, the power of the powder mixer is 2kw.
[0032] Furthermore, in step 1, the expanded graphite is first added into the mixer and stirred at a speed of 300 r / min. While maintaining the speed, graphene is added and stirred continuously. Finally, the carbon fiber is added, the speed is increased to 500 r / min, and stirring and mixing are continued for 3 hours.
[0033] Furthermore, in step 2, the isostatic pressing pressure is 100-200 MPa, the temperature is 2000-2400° C., and the time is 1-2 h.
[0034] Furthermore, the power of the isostatic pressing is 3kw.
[0035] Furthermore, before isostatic pressing the mixed material in step 2, the mixed material is first poured into a compression mold, and after isostatic pressing, the mixed material is taken out from the compression mold to obtain a crucible preform.
[0036] Furthermore, the heating temperature for sintering in step 3 is 1400-2000°C and the vacuum degree is 10 -1 -10 -5Pa, pressure is 100-200 MPa, time is 2-3h.
[0037] Furthermore, the sintering equipment in step 3 is a vacuum atmosphere furnace, and the gas used in the vacuum atmosphere furnace is one of nitrogen or argon.
[0038] Furthermore, the power of the vacuum atmosphere furnace is 90kw.
[0039] Furthermore, in step 3, during the sintering process of the crucible preform, an external clamp coupled to the structure of the crucible preform is used to fix the crucible preform to prevent deformation.
[0040] Furthermore, the materials used for the molding die and the external clamp are both stainless steel.
[0041] The present invention also provides an application of the molded crucible, wherein the molded crucible is used in a single crystal furnace, a silicon carbide crystal growth furnace, or in a process of preparing a negative electrode material.
[0042] The beneficial effects of the present invention are: 1. The present invention selects expanded graphite with specific parameters, whose internal structure is non-dense and has a porous structure and a compression space. The graphene and / or the carbon fiber are inserted into the porous structure of the expanded graphite during the molding process to form an interlaced and dense network structure, thereby improving the bonding interface between the materials. After molding, the interlaced network structure is fixed, and the obtained thickness is 4-6 mm, the ash content is 154-205 ppm, the compressive strength is 102-130 MPa, the flexural strength is 60-85 MPa, the elastic modulus is 15-17 MPa, and the expansion coefficient is (3-4)×10 -6 / ℃, bulk density is 1.6-1.7g / cm 3 Molded crucibles; 2. The molded crucible prepared by the present invention is molded once, has precise dimensions, and few defects. Compared with the traditional carbon-carbon crucible, the molded crucible has a reduced thickness (the thickness of the manufactured crucible is 4-6 mm, and the thickness of the external mesh crucible is about 12-15 mm). The molded crucible prepared by the present invention is 16-36% thinner than the traditional carbon-carbon crucible, which saves materials and reduces the overall cost. 3. There are a large number of carbon-carbon composite materials and products used in the photovoltaic thermal field industry, but they experience carbon corrosion and silicon erosion during long-term use, thereby generating waste / slag (polysilicon deposition, silicon oxides, silicon carbides, carbon powder, carbon oxides, metal impurities in silicon raw materials, metal impurities introduced by equipment components, etc.). The corroded surface has many problems such as low thermal conductivity, insufficient strength, dimensional deviation, and appearance deformation. Therefore, the waste / slag is recycled and subjected to a series of processing procedures such as impurity removal (hydrochloric acid dissolves metal impurities such as iron, aluminum, calcium, chromium, nickel, etc.), crushing, grading, and grinding, so that the usable part is turned into treasure, and the raw materials of the chopped carbon fiber and carbon fiber powder in the present invention can be obtained, thereby further reducing costs; and after impurity removal, the chopped carbon fiber or carbon fiber powder still contains 10-20wt% of silicon and / or silicon carbide, which can play a bonding role in the molding process of the preparation process; Therefore, compared with the prior art, the above waste materials are recycled and reused, and no additional auxiliary materials such as binders (phenolic resin, furan resin, etc.) and lubricants (zinc stearate, graphite, etc.) are required. Through the stable network structure and the components of the recycled raw materials, the compressive strength, flexural strength and other properties of the molded crucible can be further improved; 4. Compared with the composite crucible made of carbon materials by chemical vapor deposition in the prior art, the molded crucible prepared by the present invention has a shorter production process and lower energy consumption; 5. The molded crucible prepared by the present invention can be used in a single crystal furnace, a silicon carbide crystal growth furnace, or in the process of preparing negative electrode materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] Figure 1 A schematic diagram of the structure of a molded crucible prepared by the present invention; Figure 2 is a SEM image of the molded crucible in Example 1 of the present invention; Figure 3 This is a SEM image of the crucible in Comparative Example 2 of the present invention. DETAILED DESCRIPTION
[0044] Example 1 The present embodiment provides a molded crucible, which is made of expanded graphite, graphene, and chopped carbon fiber in a mass ratio of 8:1:1 as raw materials through molding; the crucible has a thickness of 5 mm, an ash content of 205 ppm, a compressive strength of 124 MPa, a flexural strength of 80 MPa, an elastic modulus of 16 MPa, and an expansion coefficient of 3.5×10 -6 / ℃, bulk density is 1.65g / cm 3 .
[0045] The thickness is tested by a thickness gauge; the ash content is tested by glow discharge mass spectrometry (GDMS); the compressive strength, flexural strength and elastic modulus are tested by a universal testing machine; the expansion coefficient is tested by a thermal expansion coefficient tester; and the volume density is the ratio of the total mass to the total volume of the molded crucible.
[0046] The method for preparing the molded crucible in this embodiment comprises the following steps: Step 1: Add expanded graphite with a size of 10 μm, an expansion rate of 120 times, and a purity of 99.9% into a powder mixer for stirring at a power of 2 kW and a speed of 300 r / min; while maintaining the speed, add 1-5 layers of graphite with a size of 20 μm, an oxygen content of 20 wt%, and a Raman test D / I G =0.8, graphene with a crystallinity of 75% was continued to be stirred, and finally short-cut carbon fibers with a diameter of 7 μm and a length of 1 mm were added, and the rotation speed was increased to 500 r / min, and the stirring and mixing were continued for 3 h to obtain a mixture; Step 2, pouring the mixture into a compression mold and performing isostatic pressing, wherein the power is 3 kW, the pressure is 200 MPa, the temperature is 2000° C., and the time is 2 h. After the isostatic pressing, the crucible preform is taken out from the compression mold to obtain; Step 3: Place the crucible preform into a vacuum atmosphere furnace for sintering, wherein the power is 90 kW, the sintering heating temperature is 2000°C, and the vacuum degree is 10 -5 Pa, the pressure is 200MPa, the time is 2h, the gas used is nitrogen, and at the same time, the crucible preform is fixed by an external clamp coupled with the crucible preform structure during the sintering process to prevent deformation and obtain the molded crucible. Figure 1 In this embodiment, the materials used for the compression mold and the external fixture are stainless steel, and there is no requirement for a specific shape. The compression mold and the external fixture of different shapes can be used to prepare the compression crucible according to actual application needs. In some embodiments, the shape of the compression crucible includes but is not limited to round, square, and oval.
[0047] like Figure 2 The SEM image of the molded crucible prepared in this embodiment is shown in the figure, with a magnification of 2000 times. Figure 2 It can be clearly seen that the graphene and the carbon fiber are interspersed into the pore structure of the expanded graphite during the molding process to form an interspersed and dense network structure, thereby improving the bonding interface effect between the materials. After molding, the interspersed network structure is fixed.
[0048] Example 2 The present embodiment provides a molded crucible, which is made of expanded graphite, graphene, and carbon fiber powder in a mass ratio of 5:2:3 as raw materials through molding; the crucible has a thickness of 5 mm, an ash content of 154 ppm, a compressive strength of 102 MPa, a flexural strength of 60 MPa, an elastic modulus of 17 MPa, and an expansion coefficient of 3×10 -6 / ℃, bulk density is 1.7g / cm 3 .
[0049] The thickness is tested by a thickness gauge; the ash content is tested by glow discharge mass spectrometry (GDMS); the compressive strength, flexural strength and elastic modulus are tested by a universal testing machine; the expansion coefficient is tested by a thermal expansion coefficient tester; and the volume density is the ratio of the total mass to the total volume of the molded crucible.
[0050] The method for preparing the molded crucible in this embodiment comprises the following steps: Step 1: Add expanded graphite with a size of 5 μm, an expansion rate of 100 times, and a purity of 99.9% to a powder mixer for stirring at a power of 2 kW and a speed of 300 r / min; while maintaining the speed, add 1-5 layers of graphite with a size of 10 μm, an oxygen content of 15 wt%, and a Raman test D / I G =1. Continue stirring the graphene with a crystallinity of 65%, and finally add carbon fiber powder with a diameter of 5 μm and a length of 30 μm. After increasing the speed to 500 r / min, continue stirring and mixing for 3 hours to obtain a mixture; Step 2, pouring the mixture into a compression mold and performing isostatic pressing, wherein the power is 3 kW, the pressure is 100 MPa, the temperature is 2100° C., and the time is 1 hour. After the isostatic pressing, the crucible preform is taken out from the compression mold to obtain; Step 3: Place the crucible preform into a vacuum atmosphere furnace for sintering, wherein the power is 90 kW, the sintering heating temperature is 1400°C, and the vacuum degree is 10 -5 Pa, the pressure is 200 MPa, the time is 3h, and the gas used is nitrogen. At the same time, during the sintering process, the crucible preform is fixed with an external clamp coupled to the crucible preform structure to prevent deformation and obtain the molded crucible.
[0051] Example 3 The present embodiment provides a molded crucible, which is made of expanded graphite, graphene, and chopped carbon fiber in a mass ratio of 3:1:1 as raw materials through molding; the crucible has a thickness of 5 mm, an ash content of 190 ppm, a compressive strength of 109 MPa, a flexural strength of 72 MPa, an elastic modulus of 17 MPa, and an expansion coefficient of 3×10 -6 / ℃, bulk density is 1.6g / cm 3 .
[0052] The thickness is tested by a thickness gauge; the ash content is tested by glow discharge mass spectrometry (GDMS); the compressive strength, flexural strength and elastic modulus are tested by a universal testing machine; the expansion coefficient is tested by a thermal expansion coefficient tester; and the volume density is the ratio of the total mass to the total volume of the molded crucible.
[0053] The method for preparing the molded crucible in this embodiment comprises the following steps: Step 1: Add expanded graphite with a size of 10 μm, an expansion rate of 120 times, and a purity of 99.9% into a powder mixer for stirring at a power of 2 kW and a speed of 300 r / min; while maintaining the speed, add 1 to 5 layers of graphite with a size of 10 μm, an oxygen content of 20 wt%, and a Raman test D / I G =1. Continue stirring the graphene with a crystallinity of 65%, and finally add chopped carbon fibers with a diameter of 7 μm and a length of 1 mm, increase the speed to 500 r / min, and continue stirring and mixing for 3 hours to obtain a mixture; Step 2, pouring the mixture into a compression mold and performing isostatic pressing, wherein the power is 3 kW, the pressure is 100 MPa, the temperature is 2200° C., and the time is 2 h. After the isostatic pressing, the crucible preform is taken out from the compression mold to obtain; Step 3: Place the crucible preform into a vacuum atmosphere furnace for sintering, wherein the power is 90 kW, the sintering heating temperature is 1800°C, and the vacuum degree is 10 -5 Pa, the pressure is 100 MPa, the time is 3 hours, and the gas used is nitrogen. At the same time, during the sintering process, the crucible preform is fixed with an external clamp coupled to the crucible preform structure to prevent deformation and obtain the molded crucible.
[0054] Example 4 The present embodiment provides a molded crucible, which is made of expanded graphite, graphene, and carbon fiber powder in a mass ratio of 3:1:1 as raw materials through molding; the crucible has a thickness of 5 mm, an ash content of 163 ppm, a compressive strength of 110 MPa, a flexural strength of 65 MPa, an elastic modulus of 15.5 MPa, and an expansion coefficient of 3.4×10 -6 / ℃, bulk density is 1.68g / cm 3 .
[0055] The thickness is tested by a thickness gauge; the ash content is tested by glow discharge mass spectrometry (GDMS); the compressive strength, flexural strength and elastic modulus are tested by a universal testing machine; the expansion coefficient is tested by a thermal expansion coefficient tester; and the volume density is the ratio of the total mass to the total volume of the molded crucible.
[0056] The method for preparing the molded crucible in this embodiment comprises the following steps: Step 1: Add expanded graphite with a size of 5 μm, an expansion rate of 100 times, and a purity of 99.9% to a powder mixer for stirring at a power of 2 kW and a speed of 300 r / min; while maintaining the speed, add 1-5 layers of graphite with a size of 20 μm, an oxygen content of 15 wt%, and a Raman test D / I G =0.8, graphene with a crystallinity of 75% was continued to be stirred, and finally carbon fiber powder with a diameter of 6 μm and a length of 20 μm was added, and the speed was increased to 500 r / min, and the stirring and mixing were continued for 3 h to obtain a mixture; Step 2, pouring the mixture into a compression mold and performing isostatic pressing, wherein the power is 3 kW, the pressure is 200 MPa, the temperature is 2300° C., and the time is 1 hour. After the isostatic pressing, the crucible preform is taken out from the compression mold to obtain; Step 3: Place the crucible preform into a vacuum atmosphere furnace for sintering, wherein the power is 90 kW, the sintering heating temperature is 2000°C, and the vacuum degree is 10 -4 Pa, the pressure is 150 MPa, the time is 2 h, and the gas used is nitrogen. At the same time, during the sintering process, the crucible preform is fixed with an external clamp coupled to the crucible preform structure to prevent deformation and obtain the molded crucible.
[0057] Example 5 The present embodiment provides a molded crucible, which is made of expanded graphite, graphene, chopped carbon fiber, and carbon fiber powder in a mass ratio of 5:2:1:2 as raw materials through molding; the crucible has a thickness of 5 mm, an ash content of 182 ppm, a compressive strength of 118 MPa, a flexural strength of 78 MPa, an elastic modulus of 17 MPa, and an expansion coefficient of 3×10 -6 / ℃, bulk density is 1.7g / cm 3 .
[0058] The thickness is tested by a thickness gauge; the ash content is tested by glow discharge mass spectrometry (GDMS); the compressive strength, flexural strength and elastic modulus are tested by a universal testing machine; the expansion coefficient is tested by a thermal expansion coefficient tester; and the volume density is the ratio of the total mass to the total volume of the molded crucible.
[0059] The method for preparing the molded crucible in this embodiment comprises the following steps: Step 1: Add expanded graphite with a size of 10 μm, an expansion rate of 100 times, and a purity of 99.9% to a powder mixer for stirring at a power of 2 kW and a speed of 300 r / min; while maintaining the speed, add 1 to 5 layers of graphite with a size of 10 μm, an oxygen content of 20 wt%, and a Raman test D / I G =0.8, and graphene with a crystallinity of 65% was continued to be stirred, and finally short-cut carbon fibers with a diameter of 7 μm and a length of 1 mm and carbon fiber powder with a diameter of 3 μm and a length of 30 μm were added, and the speed was increased to 500 r / min, and the stirring and mixing were continued for 3 h to obtain a mixture; Step 2, pouring the mixture into a compression mold and performing isostatic pressing, wherein the power is 3 kW, the pressure is 200 MPa, the temperature is 2400° C., and the time is 2 h. After the isostatic pressing, the crucible preform is taken out from the compression mold to obtain; Step 3: Place the crucible preform into a vacuum atmosphere furnace for sintering, wherein the power is 90 kW, the sintering heating temperature is 2000°C, and the vacuum degree is 10 -5 Pa, the pressure is 200 MPa, the time is 2h, the gas used is nitrogen, and at the same time, during the sintering process, the crucible preform is fixed with an external clamp coupled to the crucible preform structure to prevent deformation to obtain the molded crucible.
[0060] Example 6 The present embodiment provides a molded crucible, which is made of expanded graphite, graphene, and chopped carbon fiber in a mass ratio of 8:1:1 as raw materials through molding; the crucible has a thickness of 5 mm, an ash content of 201 ppm, a compressive strength of 130 MPa, a flexural strength of 85 MPa, an elastic modulus of 17 MPa, and an expansion coefficient of 3.5 × 10 -6 / ℃, bulk density is 1.7 g / cm 3 .
[0061] The thickness is tested by a thickness gauge; the ash content is tested by glow discharge mass spectrometry (GDMS); the compressive strength, flexural strength and elastic modulus are tested by a universal testing machine; the expansion coefficient is tested by a thermal expansion coefficient tester; and the volume density is the ratio of the total mass to the total volume of the molded crucible.
[0062] The method for preparing the molded crucible in this embodiment comprises the following steps: Step 1: Add expanded graphite with a size of 10 μm, an expansion rate of 120 times, and a purity of 99.9% into a powder mixer for stirring at a power of 2 kW and a speed of 300 r / min; while maintaining the speed, add 1-5 layers of graphite with a size of 20 μm, an oxygen content of 20 wt%, and a Raman test D / I G =0.8, graphene with a crystallinity of 75% was continued to be stirred, and finally short-cut carbon fibers with a diameter of 7 μm and a length of 1 mm were added, and the rotation speed was increased to 500 r / min, and the stirring and mixing were continued for 3 h to obtain a mixture; In this embodiment, the chopped carbon fiber is made of carbon-carbon composite materials and product waste recycled from the photovoltaic thermal field industry through existing recycling processes, wherein the silicon content is 3-7wt% and the silicon carbide content is 8-12wt%; Step 2, pouring the mixture into a compression mold and performing isostatic pressing, wherein the power is 3 kW, the pressure is 200 MPa, the temperature is 2000° C., and the time is 2 h. After the isostatic pressing, the crucible preform is taken out from the compression mold to obtain; Step 3: Place the crucible preform into a vacuum atmosphere furnace for sintering, wherein the power is 90 kW, the sintering heating temperature is 2000°C, and the vacuum degree is 10 -5 Pa, the pressure is 200 MPa, the time is 2 hours, the gas used is nitrogen, and at the same time, during the sintering process, the crucible preform is fixed with an external clamp coupled to the crucible preform structure to prevent deformation to obtain the molded crucible.
[0063] Example 7 The present embodiment provides a molded crucible, which is made of expanded graphite, graphene, and carbon fiber powder in a mass ratio of 5:2:3 as raw materials through molding; the crucible has a thickness of 5 mm, an ash content of 198 ppm, a compressive strength of 103 MPa, a flexural strength of 62 MPa, an elastic modulus of 17 MPa, and an expansion coefficient of 3×10 -6 / ℃, bulk density is 1.7g / cm 3 .
[0064] The thickness is tested by a thickness gauge; the ash content is tested by glow discharge mass spectrometry (GDMS); the compressive strength, flexural strength and elastic modulus are tested by a universal testing machine; the expansion coefficient is tested by a thermal expansion coefficient tester; and the volume density is the ratio of the total mass to the total volume of the molded crucible.
[0065] The method for preparing the molded crucible in this embodiment comprises the following steps: Step 1: Add expanded graphite with a size of 5 μm, an expansion rate of 100 times, and a purity of 99.9% to a powder mixer for stirring at a power of 2 kW and a speed of 300 r / min; while maintaining the speed, add 1-5 layers of graphite with a size of 10 μm, an oxygen content of 15 wt%, and a Raman test D / I G =1. Continue stirring the graphene with a crystallinity of 65%, and finally add carbon fiber powder with a diameter of 5 μm and a length of 30 μm. After increasing the speed to 500 r / min, continue stirring and mixing for 3 hours to obtain a mixture; In this embodiment, the carbon fiber powder is made of carbon-carbon composite materials and product waste recycled from the photovoltaic thermal field industry through existing recycling processes, wherein the silicon content is 1-5wt% and the silicon carbide content is 6-10wt%; Step 2, pouring the mixture into a compression mold and performing isostatic pressing, wherein the power is 3 kW, the pressure is 100 MPa, the temperature is 2100° C., and the time is 1 hour. After the isostatic pressing, the crucible preform is taken out from the compression mold to obtain; Step 3: Place the crucible preform into a vacuum atmosphere furnace for sintering, wherein the power is 90 kW, the sintering heating temperature is 1400°C, and the vacuum degree is 10 -5 Pa, the pressure is 200 MPa, the time is 3h, and the gas used is nitrogen. At the same time, during the sintering process, the crucible preform is fixed with an external clamp coupled to the crucible preform structure to prevent deformation and obtain the molded crucible.
[0066] Comparing Example 1 with Example 6, and Example 2 with Example 7, it can be seen that the chopped carbon fiber and carbon fiber powder obtained by using recycled carbon-carbon composite materials and product waste after impurity removal in the existing recycling process can play a bonding role in the molding process of the preparation process because they contain 10-20wt% of silicon and / or silicon carbide. This is mainly because when silicon or silicon carbide is in a high-temperature molten state, due to factors such as the surface tension and fluidity of the liquid, it can produce a certain adhesion phenomenon with the material in contact with it. After impurity removal, silicon can be filled in the crystal gap or interact with the fibrous reinforcement material (such as carbon fiber), thereby improving the compressive strength and flexural strength of the material and achieving the purpose of dispersion strengthening. This makes the compressive strength and flexural strength of Example 6 and Example 7 improved to a certain extent. Therefore, compared with the prior art, the above-mentioned waste materials are recycled and reused, and no additional auxiliary materials such as adhesives (phenolic resin, furan resin, etc.) and lubricants (zinc stearate, graphite, etc.) are required. Through the stable network structure and the components of the recycled raw materials, the compressive strength, flexural strength and other properties of the molded crucible can be further improved compared with directly purchased carbon fibers.
[0067] Comparative Example 1 The comparative example provides a crucible, which is made of expanded graphite and chopped carbon fiber in a mass ratio of 4:1 as raw materials by molding; the crucible has a thickness of 5 mm, an ash content of 135 ppm, a compressive strength of 91 MPa, a flexural strength of 50 MPa, an elastic modulus of 13 MPa, and an expansion coefficient of 4×10 -6 / ℃, bulk density is 1.75g / cm 3 .
[0068] The thickness is tested by a thickness gauge; the ash content is tested by glow discharge mass spectrometry (GDMS); the compressive strength, flexural strength and elastic modulus are tested by a universal testing machine; the expansion coefficient is tested by a thermal expansion coefficient tester; and the volume density is the ratio of the total mass of the crucible to the total volume.
[0069] The preparation method of the crucible in this comparative example comprises the following steps: Step 1, adding expanded graphite with a size of 10 μm, an expansion rate of 120 times, and a purity of 99.9% into a powder mixer for stirring, with a power of 2 kW and a rotation speed of 300 r / min; adding short-cut carbon fiber with a diameter of 7 μm and a length of 1 mm, increasing the rotation speed to 500 r / min, and continuously stirring and mixing for 3 hours to obtain a mixture; Step 2, pouring the mixture into a compression mold and performing isostatic pressing, wherein the power is 3 kW, the pressure is 200 MPa, the temperature is 2000° C., and the time is 2 h. After the isostatic pressing, the crucible preform is taken out from the compression mold to obtain; Step 3: Place the crucible preform into a vacuum atmosphere furnace for sintering, wherein the power is 90 kW, the sintering heating temperature is 2000°C, and the vacuum degree is 10 -5 Pa, the pressure is 180 MPa, the time is 2 hours, the gas used is nitrogen, and at the same time, during the sintering process, the crucible preform is fixed with an external clamp coupled to the crucible preform structure to prevent deformation to obtain the crucible.
[0070] Comparative Example 1 and Examples 1-5 are compared. No graphene is added to Comparative Example 1, so the expanded graphite and the chopped carbon fibers in the crucible do not form a dense network connection, the crystallinity is poor, the network structure is not fixed after molding, and the overall performance is poor.
[0071] Comparative Example 2 The comparative example provides a crucible, which is made of expanded graphite, graphene, and chopped carbon fiber in a mass ratio of 8:1:1 by molding; the crucible has a thickness of 5 mm, an ash content of 425 ppm, a compressive strength of 107 MPa, a flexural strength of 55 MPa, an elastic modulus of 15 MPa, and an expansion coefficient of 3×10 -6 / ℃, bulk density is 1.6g / cm 3 .
[0072] The thickness is tested by a thickness gauge; the ash content is tested by glow discharge mass spectrometry (GDMS); the compressive strength, flexural strength and elastic modulus are tested by a universal testing machine; the expansion coefficient is tested by a thermal expansion coefficient tester; and the volume density is the ratio of the total mass of the crucible to the total volume.
[0073] The preparation method of the crucible in this comparative example comprises the following steps: Step 1: Add expanded graphite with a size of 10 μm, an expansion rate of 120 times, and a purity of 99.9% into a powder mixer for stirring at a power of 2 kW and a speed of 300 r / min; while maintaining the speed, add 1-5 layers of graphite with a size of 30 μm, an oxygen content of 30 wt%, and a Raman test D / I G =1.2, graphene with a crystallinity of 50% was continued to be stirred, and finally short-cut carbon fibers with a diameter of 7 μm and a length of 3 mm were added, and the rotation speed was increased to 500 r / min, and the stirring and mixing were continued for 3 h to obtain a mixture; Step 2, pouring the mixture into a compression mold and performing isostatic pressing, wherein the power is 3 kW, the pressure is 200 MPa, the temperature is 2400° C., and the time is 2 h. After the isostatic pressing, the crucible preform is taken out from the compression mold to obtain; Step 3: Place the crucible preform into a vacuum atmosphere furnace for sintering, wherein the power is 90 kW, the sintering heating temperature is 1400°C, and the vacuum degree is 10 -5 Pa, the pressure is 200 MPa, the time is 2h, the gas used is nitrogen, and at the same time, during the sintering process of the crucible preform, the crucible preform is fixed with an external clamp coupled to the crucible preform structure to prevent deformation to obtain the crucible.
[0074] Comparing Comparative Example 2 with Examples 1-5, the graphene added in Comparative Example 2 has a high oxidation degree and a low crystallinity. Figure 3 As shown, it is a SEM picture of the crucible in this comparative example, and the magnification is 2000 times. It can be seen from the picture that the crucible of this comparative example does not form an interlaced and dense network structure, so the overall strength of the crucible is lower than that of the embodiment.
[0075] Comparative Example 3 The crucible was prepared by chemical vapor deposition method in the prior art. The crucible had a thickness of 5 mm, an ash content of 148 ppm, a compressive strength of 88 MPa, a flexural strength of 47 MPa, an elastic modulus of 15 MPa, and an expansion coefficient of 3×10 -6 / ℃, bulk density is 1.72g / cm 3 . The total time for preparing the crucible is 360 h, which is much longer than the preparation time of 6 h to 8 h in the embodiment. The cost is 3 times that of embodiment 1, and the energy consumption is 36000 kw·h, which is increased by 30 times.
[0076] It should be understood that the present invention is not limited to what has been described above and shown in the accompanying drawings, and that various modifications and changes may be made without departing from the scope thereof. The scope of the present invention is limited only by the appended claims.
Claims
1. A molded crucible, characterized in that: The molded crucible is made of expanded graphite, graphene and carbon fiber as raw materials through molding, and the graphene and / or carbon fiber are inserted into the pore structure of the expanded graphite during the molding process to obtain the molded crucible; The thickness of the crucible is 4-6 mm, the ash content is 154-205 ppm, the compressive strength is 102-130 MPa, the flexural strength is 60-85 MPa, the elastic modulus is 15-17 MPa, and the expansion coefficient is (3-4)×10 -6 / ℃, bulk density is 1.6-1.7g / cm 3 .
2. The molded crucible according to claim 1, characterized in that: The mass ratio of the expanded graphite, graphene and carbon fiber is (50-80): (10-20): (10-30).
3. The molded crucible according to claim 1, characterized in that: The size of the expanded graphite is 5-10 μm; the expansion rate of the expanded graphite is 100-120 times; and the purity of the expanded graphite is ≥99.9%.
4. The molded crucible according to claim 1, characterized in that: The number of layers of the graphene is 1-5; the size of the graphene is 10-20 μm; the oxygen content of the graphene is 15-20 wt%; the I D / I G =0.8-1; the crystallinity of the graphene is 65-75%.
5. The molded crucible according to claim 1, characterized in that: The carbon fiber is one or more of chopped carbon fiber and carbon fiber powder.
6. The molded crucible according to claim 5, characterized in that: The diameter of the chopped carbon fiber is 5-15 μm and the length is 1-2 mm; or the diameter of the carbon fiber powder is 5-15 μm and the length is 20-200 μm.
7. The molded crucible according to claim 5, characterized in that: When the carbon fiber includes chopped carbon fiber and carbon fiber powder, the mass ratio of the chopped carbon fiber to the carbon fiber powder is 1:
2.
8. A method for preparing the molded crucible according to any one of claims 1 to 7, characterized in that: The steps include: Step 1, adding expanded graphite, graphene, and carbon fiber into a mixer in the order of adding them, stirring them, and obtaining a mixture; Step 2, isostatically pressing the mixed material to obtain a crucible preform; Step 3: sintering the crucible preform to obtain the molded crucible.
9. The method for preparing a molded crucible according to claim 8, characterized in that: The stirring speed in step 1 is 300-1000r / min, and the time is 2-5h; In step 2, the isostatic pressing pressure is 100-200 MPa, the temperature is 2000-2400°C, and the time is 1-2 hours; The heating temperature for sintering in step 3 is 1400-2000°C and the vacuum degree is 10 -1 -10 -5 Pa, pressure is 100-200 MPa, time is 2-3h.
10. Use of the molded crucible according to any one of claims 1 to 7, characterized in that: The molded crucible is used in a single crystal furnace, a silicon carbide crystal growth furnace, or in the preparation process of negative electrode materials.
Citation Information
Patent Citations
Expandable graphite sheet, method for protecting carbonaceous crucible using the expandable graphite sheet, and single crystal pulling apparatus
CN101657570A
Preparation method of carbon / carbon composite material crucible
CN112028657A
Composite crucible and preparation method and application thereof
CN117088703A